Complex picture for likelihood of ENSO-driven flood hazard - R. Emerton (Nature Portfolio, 2017)
El Niño and La Niña (ENSO) events influence global river flow and are often used as an early indicator of potential flooding. Here, the authors show that the probability of ENSO-driven flood hazard is more complex than is often perceived, and highlight the importance of considering hydrological response.